Baricitinib Therapy for Moderate to Severe Alopecia Areata: A Retrospective Review of 95 Japanese Patients - Takafumi Numata; Ryokichi Irisawa; Miho Mori; Masaki Uchiyama; Kazutoshi Harada (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)